PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP BELANJA MODAL PADA KABUPATEN DAN KOTA DI JAWA TENGAH PERIODE 2021-2024 - Risa Mayyuhanikmah; LMS Kristiyanti; Darmanto Darmanto (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), and Budget Financing Surplus (SiLPA) on Capital Expenditure in Regencies/Cities in Central Java for the period 2021–2024. Using secondary data from the Directorate General of Taxes (DJPK) with a sample of 140 observations (35 regencies/cities × 4 years) and multiple linear regression analysis, the results show that PAD (t=16.935; sig. 0.000) and DAU (t=4.796; sig. 0.000) have a positive and significant effect on Capital Expenditure, while SiLPA (t=-0.147; sig. 0.883) has no significant effect. Simultaneously, the third variable has a significant effect (F=143.894; sig. 0.000) with a contribution of 75.5% (Adjusted R²=0.755). This finding confirms that increasing PAD and DAU boosts regional capacity to finance infrastructure development, while SiLPA is more directed at covering deficits and short-term routine spending.